2013
DOI: 10.1115/1.4025127
|View full text |Cite
|
Sign up to set email alerts
|

Control of a Supercritical CO2 Recompression Brayton Cycle Demonstration Loop

Abstract: The U.S. Department of Energy is currently focused on the development of nextgeneration nuclear power reactors, with an eye towards improved efficiency and reduced capital cost. To this end, reactors using a closed-Brayton power conversion cycle have been proposed as an attractive alternative to steam turbines. The supercritical-C02 recompression cycle has been identified as a leading candidate for this application since it can achieve high efficiency at relatively low operating temperatures with extremely com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…The interest in CO 2 based cycles arises as a part of our effort to explore them for possible power generation using CSP [1,19]. There have been some studies suggesting the use of supercritical CO 2 for nuclear power generation also [19][20][21][22][23][24][25].…”
Section: Performance Evaluation Of Co 2 Brayton Cyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…The interest in CO 2 based cycles arises as a part of our effort to explore them for possible power generation using CSP [1,19]. There have been some studies suggesting the use of supercritical CO 2 for nuclear power generation also [19][20][21][22][23][24][25].…”
Section: Performance Evaluation Of Co 2 Brayton Cyclesmentioning
confidence: 99%
“…The objective of this paper is to further explore the above two path function coordinate system to understand the intricate link between the performance indicators and cycle operating parameters for the specific case of CO 2 Brayton cycle power plants. This study is motivated by recent developments in concentrated solar power using CO 2 based Brayton cycles [1,2,[18][19][20][21][22][23][24][25]. Recently, Mohagheghi et al [26] used Pareto-based multi objective optimization for optimizing the process parameters of transcritical regenerative CO 2 Brayton cycle.…”
Section: Introductionmentioning
confidence: 98%
“…An immersion type of electric heater was used to make a high-temperature supercritical CO 2 , and two printed circuit heat exchangers (PCHEs) were manufactured as a recuperator. In recent publication [6,7], experimental results obtained in 2012 showed that net power of 15 kWe was generated at 10,500 kPa/477°C/50,000 rpm operating conditions. Bechtel Marine Propulsion Corporation (BMPC) including Knolls Atomic Power Laboratory and Bettis Atomic Power Laboratory also designed and built a 100-kWe supercritical CO 2 Brayton cycle integrated systems test experimental apparatus for evaluating the applicability of a supercritical CO 2 power generation system in a nuclear propulsion shipboard [8][9][10][11].…”
Section: Introductionmentioning
confidence: 96%
“…Sandia National Lab (SNL) has been implementing and improving a supercritical CO 2 power generation test loop since 2005 [4][5][6][7]. In collaboration with Barber-Nichols, SNL has developed technologies for the key components of supercritical CO 2 power generation systems and conducted compressor tests Turbomachinery for the supercritical carbon dioxide power cycle J.…”
Section: Introductionmentioning
confidence: 99%
“…SNL studied the Brayton power cycle using different ideal gases, far from their critical point in 2006 [30]. This analysis entailed to the S-CO 2 power cycle, constructing a compressor loop and a complete cycle in unrecuperated layout [31], a recuperated layout [32] and finally a re-compression layout [33]. Future plans include the construction of the Nuclear Energy System Laboratory/Brayton Lab, with a 10 MWe power plant for SFR in 2020 [34].…”
Section: Introductionmentioning
confidence: 99%